Can Caffeine Be an Effective Ergogenic Aid in Combat Sports? A Comprehensive Review - Komorowski, Marcin; Janiszewski, Michał; Pelczarska, Aleksandra; Kaczorowski, Rafal; Forenc, Tomasz; Hunia, Jaromir; Górny, Julia; Jurek, Jonasz; Kapciak, Alicja (Journal of Education, Health and Sport, 2025)
Introduction: Caffeine, a well-known stimulant, is commonly used by athletes to enhance performance across various sports, including combat sports. Its ergogenic properties, such as improved strength, endurance, and cognitive function, have been well documented in the literature. This paper explores the effects of caffeine supplementation on combat sports, specifically in disciplines such as judo, jiu-jitsu, taekwondo, and boxing. The impact of different doses of caffeine on performance in these sports is examined, along with potential risks, limitations, and considerations for its use. Aim of Study: The primary aim of this study is to analyze the effects of caffeine on performance in combat sports, considering various factors such as optimal dosage, timing, and the impact of habitual caffeine consumption. Additionally, this paper evaluates the potential adverse effects, including anxiety, sleep disturbances, and cardiovascular concerns, as well as the considerations regarding caffeine’s status as a banned substance in sports. Material and methods: A review of the literature on caffeine and its effect was performed using the PubMed database. Results and Conclusions: Caffeine supplementation consistently enhances performance in combat sports. Doses ranging from 3–6 mg/kg were found to improve strength, endurance, and reaction times across various combat sports, with higher doses being more effective for elite athletes. However, habitual caffeine consumption may diminish responsiveness to caffeine’s ergogenic effects. Caffeine’s potential adverse effects, such as anxiety, insomnia, and increased heart rate, were reported, with gender differences in sensitivity. While caffeine’s ergogenic effects are well-established, its use should be personalized, considering individual responses and training status. Furthermore, caffeine’s legal status and potential interactions with other substances, such as alcohol and medications, must be considered in competitive settings.